Property and Speech - Robert Allen Sedler (Washington University Journal of Law & Policy, 2006)
This Essay analyzes the impact of the First Amendment’s guarantee of freedom of speech on the use, enjoyment and control of property. The Essay analyzes this impact with reference to “The First Amendment as Sword” and “The First Amendment as Shield.” In “The First Amendment as Sword,” the Essay discusses how the First Amendment has been asserted to interfere with a property owner’s use or control of tangible property and to limit the protection of an owner’s property interests. The following areas will be covered: (1) Picketing and Protests; (2) Boycotts; (3) Governmental Economic Regulation; (4) Home Solicitation; (5) “Fair Use” and Copyright Protection; and (6) Access to Public Property. In “The First Amendment as Shield,” the Essay discusses how the First Amendment has been asserted to invalidate or limit otherwise permissible government regulation of property ownership or use by enterprises engaged in the “business of expression.” The following areas will be covered: (1) Regulation of Sexually-Oriented Entertainment; (2) Licensing of the Business of Expression; (3) Billboard and Sign Regulation; (4) Illegal Conduct and the Business of Expression; (5) Regulation of Newspapers and Publishers; and (6) Regulation of Broadcasting, Cable and the Internet. The Essay concludes, not surprisingly, that the First Amendment’s guarantee of freedom of expression has a very significant impact on the use, enjoyment and control of property. The First Amendment operates as a sword to enable persons engaged in expressive activity to interfere with an owner’s use or control of tangible property and to avoid liability for interference with an owner’s property interests. The First Amendment also operates as a shield to invalidate or limit otherwise permissible regulation of property use and business operations by enterprises engaged in the “business of expression.”
Keywords: First Amendment protections (United States Constitution); Freedom of speech; Intellectual property law; Property rights; United States Constitution; United States